Changes in Caregiver Health in the Years Surrounding the Birth of a Child With Health Problems: Administrative Data From British Columbia. Issue 5 (May 2019) - Brehaut, Jamie C.; Guèvremont, Anne; Arim, Rubab G.; Garner, Rochelle E.; Miller, Anton R.; McGrail, Kimberlyn M.; Brownell, Marni; Lach, Lucy M.; Rosenbaum, Peter L.; Kohen, Dafna E.
Abstract : Background: Caregivers of children with health problems (CHPs; usually mothers) experience more physical and psychological health problems than those of children without health problems (non-CHPs). Primarily cross-sectional and survey-driven, this literature has not yet explored whether these health differences existed before the birth of the CHPs, or are exacerbated postbirth. Methods: Using linked administrative health data on all mother-child dyads for children born in the year 2000 in British Columbia, Canada, we examined maternal health before, during, and after the birth of CHPs, and compared it between mothers of CHPs and non-CHPs with piecewise growth curve modeling. Results: Compared with mothers of non-CHPs, mothers of CHPs had more physician visits (8.09 vs. 11.07), more medication types (1.81 vs. 2.60), and were more likely to be diagnosed with selected health conditions (30.9% vs. 42.5%) 4 years before the birth of the child. Over the 7-year postbirth period, the health of the 2 groups of mothers further diverged: while mothers of CHPs showed increases on physician visits and types of medication, mothers of non-CHPs did not experience any changes in physician visits and had less steep increases for types of medication. Conclusions: Health issues associated with having a child with a health problem may begin well before the birth of the child, but also appear to be exacerbated postbirth. The health challenges of caregivers of CHPs may be multifactorial, involving both preexisting conditions and the stresses associated with caring for a child with health problems. Abstract : Supplemental Digital Content is available in the text.